Innovations in the integration of advanced neuroimaging and image guided neurosurgery for the treatment of refractory brain tumors: a systematic review of clinical and functional outcomes - Amezcua, Karim Noe Zamora; Arroba, Dianna Mishell Loor; Solórzano, Vanessa De Jesús Hernández; Molina, Luisa María Ramírez; Chimbo, Yaritza Anahí Mejía; Bolaños, Alejandra Vásquez; Banda, María José Begambre (International Journal of Research in Medical Sciences, 2024)
Glioblastoma is most common and aggressive types of primary brain tumors known for its resistance to treatment. Prognosis for glioblastoma (GBM) which is an aggressive primary brain tumor, is poor. Complete resection is difficult to achieve because of tumor infiltration and extent of surgical resection is crucial for increasing survival. Compared to traditional surgery, intraoperative magnetic resonance imaging (iMRI) is prescribed as a way to improve resection accuracy. In methodology, we used PubMed, Embase, and Cochrane databases while following PRISMA-compliant systematic review through October 2024. Our designed keywords were "glioblastoma," "complete resection," "iMRI," and "overall survival." Studies focusing resection and survival results and contrasted iMRI with traditional surgery were chosen and this paper was done after screening by three reviewers. Results show fifteen studies with 2,299 glioblastoma patients were reviewed and results revealed iMRI improved the complete resection rate (68% versus 44%, OR: 2.4, p<0.001). Overall survival was higher in iMRI group (18.6 versus 13.7 months, HR: 0.76, p=0.005) and progression-free survival also improved (10.3 versus 7.5 months, HR: 0.79, p=0.004). We conclude that among patients with glioblastoma, intraoperative MRI is linked to a considerable increase in overall survival and total resection rates. The significant benefit of using iMRI in surgical practice is that it can be applied to aggressive tumors with difficult margins, and cost-effectiveness and long-term results should be the main topics of future studies.